Pelelangan Terhadap Obyek Jaminan Yang Dibebani Tiga Peringkat Hak Tanggungan Oleh Dua Badan Hukum - Roderick Dylon Kaferu (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
The Dependent Rights (HT) can be burdened with more than 1 (one) HT rating, so that the debtor can use the same collateral object as collateral for his debt. There is a situation where the debtor is 2 (two) different companies, but the management is the same. The collateral object used is the same and is burdened with 3 (three) HT levels. Credit facilities that are tied to the second-rank dependent rights have defaulted, so an auction must be held for the object of collateral. But the auction organizer rejected the auction application because it was not the first-ranked HT holder who submitted the auction. Therefore, it is a legal issue regarding the implementation of the auction of debts burdened by the second-rank HT by PT B, as well as legal protection and certainty for creditors holding second-rank HT guarantees. In this case, normative juridical law research is used by the author to carry out this writing. The author uses laws and regulations, books, and journals regarding HT and limited liability companies as primary and secondary legal materials in this writing. The results of this study show that the implementation of the auction of HT objects can be carried out, because of the existence of cross collateral and cross default deeds. Keywords: Liability; Legal Certainty; Auction.